Performance analysis on network connectivity for vehicular ad hoc networks. (2015) - Chen, Ruifeng; Zhong, Zhangdui; Chang, Chih-Yung; Ai, Bo; He, Ruisi
This paper proposes a simplified but reasonable uninterrupted highway model to evaluate the network connectivity performance for vehicular ad hoc networks (VANETs) from the view of both individual vehicle and global network. Three parameters: conditional connectivity of the communication pair of individual vehicles, global network connectivity probability, and the vehicle isolation probability are investigated. By combining the probability density function of inter-vehicle initial distance and the distribution of vehicles' relative speed, which are both derived in this paper, the closed-form of conditional connectivity is obtained. To derive the closed-forms of network connectivity and vehicle isolation probabilities, the analytical model takes into consideration the key factors such as communication range, vehicle speed, and enter intensity. The analytical results are validated by extensive simulations. Our derived highway network connectivity model could be applied in the study of a number of metrics related to connectivity in VANETs.